Design and development of diamond wire sawing setup - Tong, Pei Jue. (2012)
With fixed abrasive wire sawing technology becoming a new trend in silicon wafering processes as well as other industries that require slicing technology, the study of its efficiency becomes increasingly important. The objective of this project is to design and develop a diamond wire sawing setup that is able to assist in the study of the performance of such wafering technique.